The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/chem.201801486
|View full text |Cite
|
Sign up to set email alerts
|

C‐Functionalized Cationic Diazaoxatriangulenes: Late‐Stage Synthesis and Tuning of Physicochemical Properties

Abstract: A series of nine C‐functionalized cationic diazaoxatriangulene (DAOTA) dyes have been successfully synthesized and fully characterized, including X‐ray structural analysis of four derivatives. The introduction of electron‐withdrawing or ‐donating functions enables the tuning of both electro‐ and photochemical properties with, for instance, two consecutive (reversible) reductions or oxidations observed for nitro or amino derivatives, respectively. The substituents also impacted on the optical properties, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 60 publications
6
24
0
Order By: Relevance
“…In a different approach a range of functional groups were introduced into the DAOTA + system (1a) by electrophilic substitution exclusively in the 9 position ( Figure 1). 18 The same selectivity for the aromatic ring with the most nitrogen bridges was also found for the helicene congeners, like e.g. DMQA + (6a) reacting in the analogous 6 position (Figure 1).…”
Section: Introductionsupporting
confidence: 55%
“…In a different approach a range of functional groups were introduced into the DAOTA + system (1a) by electrophilic substitution exclusively in the 9 position ( Figure 1). 18 The same selectivity for the aromatic ring with the most nitrogen bridges was also found for the helicene congeners, like e.g. DMQA + (6a) reacting in the analogous 6 position (Figure 1).…”
Section: Introductionsupporting
confidence: 55%
“…Functionalization directly on the DAOTA + + chromophorec an roughlyb eb roken down to occur in three different regions: the positions neighboringt he O-bridge (positions 3a nd 5, Figure 1), positions neighboring the N-bridges (positions 1, 7, 9 and 11), and positions para to the carbeniumc enter (positions 2, 6a nd 10). Delgado et al (2018) have shown large effects of simple functional groups attached directly to the 9-position of DAOTA + + via electrophilic aromatic substitution, with ac lear connectionb etween electron density (donating/withdrawing groups)a nd spectral properties. [29] This is in line with observations from the DAOTA + + precursor,D MQA + + .…”
Section: Resultsmentioning
confidence: 99%
“…Delgado et al (2018) have shown large effects of simple functional groups attached directly to the 9-position of DAOTA + + via electrophilic aromatic substitution, with ac lear connectionb etween electron density (donating/withdrawing groups)a nd spectral properties. [29] This is in line with observations from the DAOTA + + precursor,D MQA + + . [30] We suspect that substitution neighboring the O-bridge is preferable to positions neighboring the N-bridge, since steric interference with the side-chain in the latter case is expected to reduce planarity.…”
Section: Resultsmentioning
confidence: 99%
“…Thus “diazaoxatrianguleniums” 162 were made via demethylation of a methyl ether in a salt 161 then intramolecular displacement of the remaining methoxyl by the so‐formed phenolic oxygen, as shown in Scheme . Electrophilic substitution of diazaoxatriangulenes such as 162 , for example nitration and Vilsmeier formylation, occurs on the benzene ring with two nitrogens attached, and ortho to a nitrogen . A study of the interaction of trianguleniums as optical probes for G‐quadruplexes, showed 163 to be a unique fluorescence probe .…”
Section: Pyrido[234‐kl]acridinementioning
confidence: 99%